PENGELOLAAN DESTINASI WISATA PANTAI GUNA MENINGKATKAN PENDAPATAN DAERAH DAN MASYARAKAT DI DESA TANJUNG LIMAU - Nurliah Nurliah; Nanda Yudha Eka Prananta; Vern Chandra; Novianti Novianti; Marlianti Bulkis; Ananta Slamet Anugrah; Rahmi Utari Razak (LOGISTA - Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
The problem that will be raised in the community service program for the Extraordinary Conditions in 2020 is the management of tourist destinations that can increase community income during the Covid-19 pandemic in Tanjung Limau Village, Muara Badak District, Kutai Kartanegara Regency. Despite the pandemic condition, the management of tourist destinations is still being carried out so that it can attract the outside community to visit Tanjung Limau Village. It is hoped that tourists can continue to increase in making visits to the tourist destinations of Jingga Beach and Panrita Lopi Beach, Tanjung Limau. Through community service programs in the management of Panrita Lopi Beach tourist destinations, awareness of the community is managed professionally. The population always strives to increase the income of the people around the coast of Tanjung Limau Village, also makes the beaches beautiful and clean so that they can attract people to visit the beach and other tours in Tanjung Limau village The method of community service programs implemented in Tanjung Limau Village is to coordinate and discuss with village officials and community leaders in the village both online and by engaging. After that, it was agreed to make several tourism management activities. Among them is making promotional videos through YouTube. The videos are taken from various tourist attractions that are busy being visited, namely Panrita Lopi Beach and Jingga Beach. Other activities include cleaning and beach services, as well as making educational posters to maintain cleanliness around the beach. The first conclusion is to increase regional income or the people of Tanjung Limau Village, the community dies on a visit to a beach tourism destination professionally in order to be able to attract local and domestic tourists to visit Tanjung Limau Village. The trick is to visit a tourist spot that is busy, namely Panrita Lopi Beach through social media, namely YouTube. Second, to increase the number of visitors at Jingga and Panrita Lopi Beaches, the beach location is tidied up and cleaned so that it is clean, orderly, and beautiful. Third, so that beach visitors in Tanjung Limau Village do not litter, then cleanliness education is carried out around the beach. The education is in the form of posters and videos of the implementation of the garbage disposal in the place. The video will be uploaded via YouTube social media so that potential visitors and beach visitors can see it. Keywords: Tourism Destinations, Promotion, Education, Tanjung Limau Village, Panrita Lopi Beach, Jingga Beach.